New euophryine jumping spiders from Central and South America (Araneae: Salticidae: Euophryinae) - Zhang, Jun-Xia; Maddison, Wayne P. (Zootaxa, 2012)
Twenty-two new species and one new genus of euophryine jumping spiders from Central America and South America aredescribed. The new genus is Ecuadattus (E. elongatus sp. nov., E. napoensis sp. nov., E. pichincha sp. nov. and the typespecies E. typicus sp. nov.). The other new species belong to the genera Amphidraus (A. complexus sp. nov.), Belliena (B.ecuadorica sp. nov.), Chapoda (C. angusta sp. nov., C. fortuna sp. nov. and C. gitae sp. nov.), Ilargus (I. foliosus sp. nov.,I. galianoae sp. nov., I. macrocornis sp. nov., I. moronatigus sp. nov., I. pilleolus sp. nov. and I. serratus sp. nov.), Maeota(M. dorsalis sp. nov., M. flava sp. nov. and M. simoni sp. nov.), Soesilarishius (S. micaceus sp. nov. and S. ruizi sp. nov.)and Tylogonus (T. parvus sp. nov. and T. yanayacu sp. nov.). Diagnostic illustrations are provided for all new species. Photographs of living spiders are also provided for some new species.